PENGARUH JUMLAH TENAGA KERJA, IPM, DAN IPTIK TERHADAP PERTUMBUHAN EKONOMI - Lazuardi, Alvin Sabastian; Muttaqin, Aminnullah Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The purpose of this study was to determine the effects of total labor, the human development index, and the information and communication technology development index on economic growth in Yogyakarta Province. This research is quantitative, using time series data. The model in this study uses multiple linear regression analysis as well as hypothesis testing and classical assumption testing. The data source used is secondary data taken from BPS for GRDP data in Yogyakarta Province, labor data, HDI data, and ICT development index data in the period 2012 to 2021. The results showed that labor and the Information and Communication Technology (ICT) development index had a significant positive effect on economic growth in Yogyakarta Province, while the Human Development Index (HDI) had a negative but insignificant effect on economic growth in Yogyakarta Province.